The Influence of Service Quality and Location on Consumer Decisions at Hotel Vista in Prabumulih - Yudi Tusri (PT. EQUATOR SINAR AKADEMIA, 2021)
This study shows that when testing the quality of service all the questions in the questionnaire are said to be valid with the provisions exceeding the value of r table where the value of r table is 0.185. And for the reliability value obtained a value of 0.849 with the provisions above 0.185 it can be said that the existing questionnaire is declared reliable for further testing. At the time of testing the location, all the questions in the questionnaire were said to be valid with the provisions exceeding the value of r table where the value of r table was 0.185. And for the reliability value obtained a value of 0.853 with the provisions above 0.185 it can be said that the existing questionnaire is declared reliable for further testing. For the calculated f value of 33,505 and for the f table value from the results of n-k-1 (n=respondent, k=independent variable) of 2.76. Thus, for the calculated f value of 33,505 > the f table value of 2.76, the service quality and location variables have a positive effect on consumer decisions.